Kajian Aspek Interior Kantor (Studi Kasus : Pt. Balai Diklat Perkretaapian): ## - Irwansyah, Irwansyah; Giovani, Giovani (Program Studi Desain Interior Unikom, 2020)
The office is a place used for business or can be referred to as the